Implentasi PSAP Nomor 13 Pada Penyajian dan Akuntabilitas Laporan Keuangan Puskesmas Modopuro - Julitha Ridha Kusuma; Maulidah Narastri (Student Research Journal, 2023)
This research was conducted to know the presentation and accountability of UPT Puskesmas Modopuro financial reports when viewed from PSAP No. 13. This study used a qualitative method with data collection techniques in three ways, namely observation, interviews, and documentation. The results of this study indicate that the presentation and accountability of the Modopuro Health Center Financial Report when viewed from PSAP Number 13 has been implemented since 2019 accompanied by a supervisor from the Health Service and its implementation has been carried out by PSAP Number 13.